2016
DOI: 10.1002/cta.2247
|View full text |Cite
|
Sign up to set email alerts
|

Matching capacitance and transfer efficiency of four wireless power transfer systems via magnetic coupling resonance

Abstract: Summary Matching capacitance determines the resonance and resonant frequency for a given wireless power transfer (WPT) system. Theoretical solutions for matching capacitance are essential to designing and controlling a coupling system in resonant status and to ensuring that the system operates under high power transfer efficiency. This paper deduced all the analytical expressions of matching capacitance to achieve magnetic resonance for four classical circuitries when considering the coils' resistances. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…For mid-range air gap between transmitting and receiving coil (the distance between two coils is usually less than eight times the diameter of the coil), the power transfer efficiency is vitally important and must be given priority in applications of high-power or continuous-operation electric devices such as power supply for household appliance, vehicle charging and microwave power transmission. Accordingly, the research on WPT technique has been mostly focused on matching impedance and controlling the system to operate at a resonant state to transfer considerable energy at high efficiency [12][13][14][15]. However, under the impedance matching condition for the maximum WPT efficiency, this study found that the power transferred to the load cannot reach the maximum when the WPT system is supplied by an AC voltage source with constant amplitude.…”
Section: Introductionmentioning
confidence: 95%
“…For mid-range air gap between transmitting and receiving coil (the distance between two coils is usually less than eight times the diameter of the coil), the power transfer efficiency is vitally important and must be given priority in applications of high-power or continuous-operation electric devices such as power supply for household appliance, vehicle charging and microwave power transmission. Accordingly, the research on WPT technique has been mostly focused on matching impedance and controlling the system to operate at a resonant state to transfer considerable energy at high efficiency [12][13][14][15]. However, under the impedance matching condition for the maximum WPT efficiency, this study found that the power transferred to the load cannot reach the maximum when the WPT system is supplied by an AC voltage source with constant amplitude.…”
Section: Introductionmentioning
confidence: 95%
“…However, sufficient practical verifications of the theory through published experimental results were not provided. Despite all four topologies of the WPT circuit being studied in References , comparison between the four topologies was limited, with no criteria provided as to which topology was most appropriate for a given system. For example, literatures on design and optimization of wireless power links initially used parallel‐primary and parallel‐secondary circuits .…”
Section: Introductionmentioning
confidence: 99%
“…Wireless power transfer (WPT) via magnetically coupled resonant circuits is receiving increased interest of scientific community due to its promising use in many industrial and biomedical applications [1][2][3][4][5][6][7] . In large part, this interest can be related to the works of Kurs et al 8 and Karalis et al 9 , where it was shown that these resonant systems allow efficient power transfer, at mid-range distances.…”
Section: Introductionmentioning
confidence: 99%